2012
DOI: 10.1002/hed.23149
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic papillary thyroid cancer with lateral neck disease: Pattern of spread by level

Abstract: We advocate for a routine excision of levels II, III, IV, and Vb in PTC with metastasize to any lateral neck level. Although we have routinely dissected level IIb, it may be appropriate to omit its dissection, as well as level Va, when there are no clinical, radiologic, or intraoperative evidence of disease involving these sublevels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
1
7
1
3
Order By: Relevance
“…In the past, the extent of surgery is generally based on the frequency and pattern of abnormal lymphatic spread. Similar to other studies, [17][18][19] we also demonstrated that level and level are the most commonly involved regions. A systematic review of 18 unique studies found that levels IIA, IIB, III, IV, and V had metastatic disease involvement in 53%, 16%, 71%, 66%, and 25% of LNDs, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In the past, the extent of surgery is generally based on the frequency and pattern of abnormal lymphatic spread. Similar to other studies, [17][18][19] we also demonstrated that level and level are the most commonly involved regions. A systematic review of 18 unique studies found that levels IIA, IIB, III, IV, and V had metastatic disease involvement in 53%, 16%, 71%, 66%, and 25% of LNDs, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Shoulder dysfunction, from injury to the spinal accessory nerve, and chyle leak are significant complications related to level II and Vb neck dissection. Previously published data, [4][5][6] including a recent large case series by our group, 10 have shown levels II and Vb to be less frequently involved with disease than levels III and IV in metastatic PTC. In this study, we aimed to identify predictors of levels II and Vb involvement in metastatic PTC with the hope of determining factors that may help limit the extent of the required neck resection.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 85%
“…сообщили о том, что частота обнаружения метастазов в ЛУ бокового уровня шеи достигает 37,7 % (обследован 501 пациент) [19]. Ряд авторов сообщает, что этот показатель варьирует от 35,5 до 74,0 % [20][21][22][23][24]. Такой разброс данных связан с тем, что число оперированных больных с метастазами в ЛУ на данных уровнях ограничено.…”
Section: рис 2 ультразвуковое исследование: а -метастаз тканевой прunclassified
“…(одноуровневое поражение -в 19,5 % случаев, многоуровневое -в 61 %) [22], M. Merdad и соавт. (многоуровневое поражение в 73 % случаев) [23], H. Keum и соавт. (множественные метастазы в 77,8 % случаев) [25].…”
Section: рис 2 ультразвуковое исследование: а -метастаз тканевой прunclassified
See 1 more Smart Citation